Sex-related differences in attention and memory - Rima Solianik; Marius Brazaitis; Albertas Skurvydas (Medicina, 2016)
Background and objectives: The sex differences and similarities in cognitive abilities is a continuing topic of major interest. Besides, the influences of trends over time and possible effects of sex steroid and assessment time on cognition have expanded the necessity to re-evaluate differences between men and women. Therefore, the aim of this study was to compare cognitive performance between men and women in a strongly controlled experiment. Materials and methods: In total, 28 men and 25 women were investigated. Variables of body temperature and heart rate were assessed. A cognitive test battery was used to assess attention (visual search, unpredictable task switching as well as complex visual search and predictable task switching tests) and memory (forced visual memory, forward digit span and free recall test). Results: The differences in heart rate and body temperatures between men and women were not significant. There were no differences in the mean values of attention and memory abilities between men and women. Coefficients of variation of unpredictable task switching response and forward digit span were lower (P < 0.05) in men. Coefficients of variation positively correlated (P < 0.05) with attention task incorrect response and negatively correlated (P < 0.05) with correct answers in the memory task. Conclusions: Current study showed no sex differences in the mean values of cognition, whereas higher intra-individual variability of short-term memory and attention switching was identified in women, indicating that their performance was lower on these cognitive abilities.